Association between excessive maternal weight, periodontitis during the third trimester of pregnancy, and infants' health at birth - Gerson Aparecido FORATORI-JUNIOR; Bruno Gualtieri JESUINO; Rafaela Aparecida CARACHO; Eliel Soares ORENHA; Francisco Carlos GROPPO; Silvia Helena de Carvalho SALES-PERES
Abstract Excessive weight is associated with periodontitis because of inflammatory mediators secreted by the adipose tissue. Periodontal impairments can occur during pregnancy due to association between high hormonal levels and inadequate oral hygiene. Moreover, periodontitis and excessive weight during pregnancy can negatively affect an infant's weight at birth. Objective This observational, cross-sectional study aimed to evaluate the association between pre-pregnancy overweight/obesity, periodontitis during the third trimester of pregnancy, and the infants' birth weight. Methodology The sample set was divided into 2 groups according to the preconception body mass index: obesity/overweight (G1=50) and normal weight (G2=50). Educational level, monthly household income, and systemic impairments during pregnancy were assessed. Pocket probing depth (PPD) and clinical attachment level (CAL) were obtained to analyze periodontitis. The children's birth weight was classified as low (<2.5 kg), insufficient (2.5-2.999 kg), normal (3-3.999 kg), or excessive (≥4 kg). Bivariate analysis (Mann-Whitney U test, t-test, chi-squared test) and logistic regression (stepwise backward likelihood ratio) were performed (p<0.05). Results G1 showed lower socioeconomic levels and higher prevalence of arterial hypertension and gestational diabetes mellitus during pregnancy than G2 (p=0.002). G1 showed higher means of PPD and CAL (p=0.041 and p=0.039, respectively) and therefore a higher prevalence of periodontitis than G2 (p=0.0003). G1 showed lower infants' birth weight than G2 (p=0.0004). Excessive maternal weight and educational levels were independent variables associated with periodontitis during the third trimester of pregnancy (X2[2]=23.21; p<0.0001). Maternal overweight/obesity was also associated with low/insufficient birth weight (X2[1]=7.01; p=0.008). Conclusion The present findings suggest an association between excessive pre-pregnancy weight, maternal periodontitis, and low/insufficient birth weight.